Morphometric Magnetic Resonance Imaging Evaluation of Cervical Spinal Canal and Cord in Normal Small-Breed Dogs - Lee, Namsoon; Seo, Jeonghyun; Yoon, Junghee (Frontiers in Veterinary Science, 2021)
Cervical spinal disease is one of the most common neurologic disorders in small-breed dogs. Magnetic resonance imaging (MRI) has been a common test for dogs with cervical spinal diseases. However, there is no information of cervical spinal canal and cord using MRI in normal small breed-dogs. Therefore, this study aimed to perform analyses to establish morphologic MRI reference ranges of cervical spinal canal and cord in normal small-breed dogs. Cervical MRI examinations were taken in 20 client-owned small dogs. Height, width and cross-sectional area (CSA) of the spinal canal and cord were measured on sagittal and transverse T2-weighted images at each vertebral body level and each intervertebral disk level from C1-2 to C7 (total of 12 levels). The height ratio, the width ratio and the CSA ratio were calculated. The height, width, and CSA of the spinal canal and cord increased as the dog’s weight increased (P < 0.01), except for that at C1–2. However, there was no correlation between the body weight and the height ratio and the width ratio and the CSA ratio at all levels, except for that at C1–2. And there was a negative correlation between the body weight and the CSA ratio at C1–2. There were no statistical differences for the CSA of the spinal canal, the CSA of the spinal cord, and the CSA ratio between nearby levels, except for that of C1–2. There was no statistical difference between measurements in each same level of sagittal and transverse images. The results of this study may provide basic and morphometric information for diagnosing and researching cervical spinal diseases in small-breed dogs.